DOT, a videogame with no winner. Issue 2 (1st October 2012) - Roscoe, Henrique
Dot, a videogame with no winner (2011) is an audio-visual performance with synchronized sounds and images, played by a 'game console' built and programmed by the author, and controlled by retro videogame (Nintendo) joysticks. The instrument is completely autonomous and works without the need of a computer, using only a projector and a sound system to play its content. Five people from the audience are invited to play the performance along with me, adding a random aspect so that I no longer have complete control of the work. This article passes through the complete creative process of the performance, showing the artistic concept, aesthetic considerations and some generative techniques used to add some randomness to the process so that the show is different each time it is performed.